Fertility Preservation for Adolescent and Young Adult Transmen: A Case Series and Insights on Oocyte Cryopreservation - Barrett, Francesca; Shaw, Jacquelyn; Blakemore, Jennifer K.; Fino, Mary Elizabeth (Frontiers in Endocrinology, 2022)
Background: The opportunity for fertility preservation in adolescent and young adult (AYA) transmen is growing. Many AYA transmen desire future biologic children and are interested in ways to preserve fertility through oocyte cryopreservation prior to full gender affirmation, yet utilization of oocyte cryopreservation remains low. Additionally, standard practice guidelines currently do not exist for the provision of oocyte cryopreservation to AYA transmen. Our objective was to review our experience with oocyte cryopreservation in adolescent and young adult transmen in order to synthesize lessons regarding referral patterns, utilization, and oocyte cryopreservation outcomes as well as best practices to establish treatment guidance. Methods: This is a case series of all AYA transmen (aged 10 to 25 years) who contacted, consulted or underwent oocyte cryopreservation at a single high volume New York City based academic fertility center between 2009 and 2021. Results: Forty-four adolescent and young adult transmen made contact to the fertility center over the study period. Eighty percent (35/44) had a consultation with a Reproductive and Endocrinology specialist, with a median age of 16 years (range 10 to 24 years) at consultation. The majority were testosterone-naïve (71%, 25/35), and had not pursued gender affirming surgery (86%, 30/35). Expedited initiation of testosterone remained the most commonly cited goal (86%, 30/35). Fifty-seven percent (20/35) pursued oocyte cryopreservation. Ninety-five percent (19/20) underwent successful transvaginal oocyte aspiration, with a median of 22 oocytes retrieved and 15 mature oocytes cryopreserved. There were no significant adverse events. At time of review, no patient has returned to utilize their cryopreserved oocytes. Conclusions: Oocyte cryopreservation is a safe fertility preservation option in AYA transmen and is an important aspect of providing comprehensive transgender care. Insights from referral patterns, utilization, and oocyte cryopreservation outcomes from a single center’s experience with adolescent and young adult transmen can be integrated to identify lessons learned with the goal of providing transparency surrounding the oocyte cryopreservation process, improving the education and comfort of patients and providers with fertility preservation, and easing the decision to pursue an oocyte cryopreservation cycle in parallel to gender-affirmatory care.